The Influence of Organizational Communication and Organizational Communication on Employee Performance - Riambodo, Rio (Greenation Research & Yayasan Global Resarch National, 2025)
The purpose of this research is to understand and analyze: (1) Organizational Communication; (2) Organizational Communication; (3) Employee Performance; and (4) the Influence of Organizational Communication and Organizational Communication on Employee Performance at Company X in the City of Bandung, both simultaneously and partially. The research methods used in this study are descriptive surveys and explanatory surveys, with the unit of analysis being the employees of Company X in the city of Bandung, with a sample size of 50 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the research results, it was found that the Organizational Communication of Company X in Bandung City is already good, Organizational Communication in Company X in Bandung City can generally be said to be good, and the Employee Performance of Company X in Bandung City is currently rated as good. Organizational Communication and Organizational Communication simultaneously and partially influence the Employee Performance of Company X in Bandung City. However, partially, Organizational Communication dominantly influences employee performance more than Organizational Communication. Because Organizational Communication more dominantly affects employee performance, it becomes the top priority in improving employee performance. Therefore, Company X in the city of Bandung is advised to consistently maintain the existing organizational communication, so that they can work more professionally.